A spaceborne synthetic aperture radar data processor - Welsh, Simon (Department of Electrical Engineering, 2023)
This thesis is concerned with the design and implementation of a Synthetic Aperture Radar (SAR) data processor. The implementation of the processing is based on a standard sequential approach to the problem and employs commonly used algorithms. The processing was done using the C language running on an IBM Compatible Personal Computer. The raw data processed was that obtained from the Shuttle Imaging Radar B (SIRB) and was supplied by the Jet Propulsion Laboratories (JPL) in California. The basic functions performed by the software include range and azimuth processing, which involve the match filtering of reference functions with the raw data. Compensation for the effects of being a spaceborne SAR were also implemented, which involved compensation for the effect of planet rotation and radar height. Images processed by JPL of the same area were also available, which allowed for direct comparisons between the outputs of the two SAR processors. The images produced were passed through a number of filters, to improve the image quality, and resulted in favourable comparisons to the JPL generated images. The actual images are included in the later sections of the thesis.